Jews on the move implications for Jewish identity - Goldstein, Sidney; Goldstein, Alice (SUNY series in American Jewish society in the 1990s, 1996)
Based on data from the 1990 National Jewish population survey, the authors examine the high level of mobility among American Jews and their increasing dispersion throughout the United States, and how this presents new challenges to the